What is Drosophila telling us about cancer? - Lorenzo, Cécilia de; Mechler, Bernard; Bryant, Peter (Cancer and metastasis reviews, 1999)
In Drosophila, genetic loss of the tumour suppressor protein Dlg (in dlg mutants) or p127 (in lgl mutants) leads to loss of epithelial structure and excess proliferation in the imaginal discs and brain of the developing larva. These phenotypes show most of the characteristic features of human neoplasia, so study of the gene products may contribute to our understanding of cancer. Both proteins occur in high molecular-mass complexes in the membrane-associated cytoskeleton, and they both appear to play dual roles as structural proteins and active partners in signal transduction. Dlg is a membrane-associated guanylate kinase homolog (MAGUK) found at septate junctions between epithelial cells, as well as at neuromuscular junctions. Specific domains of the protein are required for membrane targeting and for localisation in junctions, and for epithelial cell proliferation control; all of these functions are probably mediated through binding to other proteins. Loss of Dlg results in the absence of septate junctions, delocalisation of several proteins including Fasciclin III, Coracle, actin and tubulin, and loss of cell polarity. p127, although mostly associated with the plasma membrane, is in most cell types also present in the cytoplasm. It shows a dynamic subcellular distribution, and its cytosolic and membrane-associated forms play distinctive roles by interacting with different binding partners, in particular the non-muscle myosin II heavy chain. Defects associated with the lgl temperature-sensitive allele include loss of the columnar organisation of epithelial cells, indicating that p127 contributes to cell structure, presumably by stabilising the plasma membrane. In addition to their organising functions, both Dlg and p127 appear to be involved in signal transduction pathways. Study of these genes shows that some proteins play both structural and functional roles, and that cancer can involve changes in the organisation of signalling pathways in addition to changes in individual pathway components.